2015
DOI: 10.1002/ehf2.12046
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and management of hospitalized and ambulatory patients with heart failure–results from ESC heart failure long‐term registry–Egyptian cohort

Abstract: Aims Our aim is to describe the clinical characteristics and management of patients hospitalized with acute heart failure (HHF) and ambulatory patients with chronic heart failure (CHF) in Egypt and compare them with heart failure (HF) patients from other countries in the European Society of Cardiology-Heart Failure (ESC-HF) registry. Methods and resultsThe ESC-HF Long-term Registry is a prospective, multi-centre, observational study of patients presenting to cardiology centres in member countries of the ESC. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 26 publications
6
64
1
4
Order By: Relevance
“…Two Egyptian studies reported that less than one quarter of their recruited HF patients had LVEF >45% 15, 19. We also reported in a recent study of hospitalized HF patients significantly dilated LV& LA dimensions, and impaired LVEF 2 .…”
Section: Discussionsupporting
confidence: 75%
“…Two Egyptian studies reported that less than one quarter of their recruited HF patients had LVEF >45% 15, 19. We also reported in a recent study of hospitalized HF patients significantly dilated LV& LA dimensions, and impaired LVEF 2 .…”
Section: Discussionsupporting
confidence: 75%
“…5,6 Briefly, this is a prospective, multi-centre, observational study of patients presenting to 211 cardiology centres of 21 European and Mediterranean countries, which are members of the ESC. 5,6 Briefly, this is a prospective, multi-centre, observational study of patients presenting to 211 cardiology centres of 21 European and Mediterranean countries, which are members of the ESC.…”
Section: Methodsmentioning
confidence: 99%
“…The present study uses data from the European Society of Cardiology Heart Failure Long-term Registry 'ESC-HF Longterm Registry', which has been reported in detail elsewhere. 5,6 Briefly, this is a prospective, multi-centre, observational study of patients presenting to 211 cardiology centres of 21 European and Mediterranean countries, which are members of the ESC. The ESC Heart Failure Association endorsed the study, which was conducted by an ad hoc Executive Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a recent analysis of a French nationwide database challenges such a standpoint, as no decline in standardized HF hospitalization rates was identified. It should be emphasized that, globally, national studies are few; most studies are either limited to a particular geographical region within a country, are part of or derived from a multicentre registry, or do not represent a nationwide sample …”
Section: Introductionmentioning
confidence: 99%